Formulation, Development, and Evaluation of Indomethacin Emulgel Using Pregelatinized Starch from Ipomoea batata Tubers - Kusuma, R (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The purpose of the present study was to develop and optimize the emulgel system for indomethacin (IND), using four types of gelling agents: Carbopol 934, HPMC K4M, xanthum gum, and pregelatinized Ipomoea batata starch (PGIBS), which are dispersed in purified water with constant stirring at a moderate speed, then the pH was adjusted to 6-6.5 using triethanolamine. Materials and Methods: The prepared emulgels were evaluated in terms of physical appearance, pH, spreadability, rheological study, viscosity, drug content determination, in vitro drug release, accelerated stability studies, and fitting of results into different kinetic equations was also carried out. Statistical Analysis Used: The Fourier transform infrared spectra of the IND and different polymers alone and in combination show the compatibility of the drug and excipients. Results: In vitro release study demonstrated diffusion controlled release of IND from formulation up to 8 h. The formulations showed higher RÂ² values for zero order plots indicating that drug release followed zero order kinetics a. The accelerated stability studies were performed according to ICH guidelines for 3 months, and the results were found to be stable in varying temperature. All the prepared emulgels showed acceptable physical properties concerning color, homogeneity, consistency, spreadability, pH value, and with higher drug release than conventional gel. Conclusion: The optimized formulations were found to be C4, H4, G4, and I4 containing a lower concentration of light castor oil and a higher concentration of emulsifiers. In the case of all evaluation parameters PGIBS and castor oilbased formulation, i.e., I4 showed better properties. So, as a general conclusion, it was suggested that the IND emulgel formulation prepared with PGIBS having the oil phase concentration in its low level and emulsifying agent concentration in its high level was the formula of choice. The results demonstrate that the release of the drug is dependent on the viscosity of the polymer used.